Effect of channel size on liquid‐liquid plug flow in small channels. Issue 1 (22nd September 2015) - Tsaoulidis, Dimitrios; Angeli, Panagiota
Abstract : The hydrodynamic properties of plug flow were investigated in small channels with 0.5‐, 1‐, and 2‐mm internal diameter, for an ionic liquid/aqueous two‐phase system with the aqueous phase forming the dispersed plugs. Bright field Particle Image Velocimetry combined with high‐speed imaging were used to obtain plug length, velocity, and film thickness, and to acquire velocity profiles within the plugs. Plug length decreased with mixture velocity, while for constant mixture velocity it increased with channel size. Plug velocity increased with increasing mixture velocity and channel size. The film thickness was predicted reasonably well for Ca  > 0.08 by Taylor's (Taylor, J Fluid Mech. 1961;10(2):161–165) model. A fully developed laminar profile was established in the central region of the plugs. Circulation times in the plugs decreased with increasing channel size. Pressure drop was predicted reasonably well by a modified literature model, using a new correlation for the film thickness derived from experimental values. © 2015 American Institute of Chemical Engineers AIChE J, 62: 315–324, 2016